Determining if brand familiarity can influence consumer’s perceptions of quality through the use of extrinsic cues, with reference to the brands of Johnnie Walker and Carling Label - Chapman, Reece (The IIE, 2016)
In today’s economic climate, competition is rife and brands are constantly looking for effective methods to establish themselves as a strong competitor in a saturated market place. Therefore strategically influencing customer behaviour to generate demand is any firm’s top priority in an attempt to sustain competitive advantage. Creating and expanding this demand is done through the influencing of a customer’s brand choice through extrinsic placebo like cues (Priilaid, 2006). This means, that consumer’s beliefs and expectations relating to the ability of product to perform, triggers a placebo effect impacting on the consequent value of the product (Shiv, Carmon & Ariely, 2005). To demonstrate the effects of subliminal stimuli on brand equity this study looks at the recent launch of Carling Blue Label. The campaign seemed to guide consumers into believing that this was a better product yet, upon closer inspection the only differentiator was that it was a single malt beer and it was in a green bottle rather than the traditional dark brown bottle. Many consumers felt at ease with this new product and felt that this was a superior product due to the similar brand associations (blue promoting excellence and quality) as the ever popular Johnnie Walker range. Results from this research report and the forthcoming conclusions can hopefully assist and guide marketers in applying their own brand stimuli in order to launch successful manipulate extrinsic cues in a lawful manner so to launch thriving product extensions and sustain competitive advantage. This research study therefore answered that there is a strategic manipulation of extrinsic cues, associated with other familiar brands and these can affect a brand’s equity, with particular reference to the Launch of Carling Blue Label. There was a relationship discovered between Johnnie Walker and Carling Blue Label.
Keywords: Brand familiarity; Brand equity; Extrinsic clues; Perceptions